SEMINAL FRUCTOSE AND CITRIC ACID CONCENTRATIONS RELATIVE TO VIRAL INFECTIONS AMONG MEN FOR FERTILITY EVALUATION IN YAOUNDE, CAMEROON - Voundi, Esther; Bih, Tanni; Nyada, Serge; Nseme, Eric; Nogue, Raissa Kamga; Mviena, Louise Nyimbe; Ayangma, Celestin Roger; Omigbodun, Akinyinka; Toukam, Michel; Aimakh, Christopher (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Introduction: Nearly 50% of infertile couples’ cases are due to male factors. Male infertility is pluri-etiological and as such, it is important to understand the role of seminal plasma novel biomarkers and viral infection in male infertility. The main objective of this study was to compare the fructose and citric acid levels in men with HBV, HCV, HIV amongst those seeking fertility evaluation. Methods: A prospective cross-sectional study was performed on consenting male participants. The semen samples from patients were collected properly and analyzed according to the World Health Organization-2010 manual. Later samples were assayed for biochemical markers and viral antigens and antibodies following their standard protocols. Statistical analysis of the findings was performed using IBM SPSS-24.0 software. Significant statistical difference between median sperm parameters of both groups of men and biomarker levels were considered at p < 0.05. Results: the prevalence of hepatitis B, C and Human Immune deficiency Virus were 6.3% (5), 2.5% (2) and 3.8% (3) respectively. The study highlighted that there is no significant difference in the fructose and citric acid levels amongst HBV, HCV, and HIV patients (p >0.05) Conclusion: The assessment of biochemical markers of seminal fluid for fertility evaluation didn’t give a clear understanding of the effect of viral infection on the accessory glands. It important to investigate in a larger population to have more pertinent information.